Fungicidal and antibacterial activity of the hydrogel compositions with silver - V. Smagin, A; V. Smagina, M; B. Kolganihina, G; B. Sadovnikova, N; Y.Gulbe, A; S. Bashina, A (International Journal of Engineering and Technology, 2018)
Contamination of the rhizosphere by pathogenic microorganisms is a universal soil-ecological problem leading to heavy losses in tuber and root crop yield of agricultural crops. Suppression of these microorganisms is possible because of special gel compositions with silver ions and nanoparticles as plant-protecting agents. An efficiency test of gel-silver inhibitors was carried out on two common pathogens, the causative agents of late blight (Oomycete Phytophthora infestans) and black leg of potato (Enterobacterium Pectobacterium atrosepticum). The study revealed an exponential relationship between  inhibitor dose and linear (by diameter) and nonlinear (by area) specific growth rates of colonies of microorganisms. According this model the EC50 values of the gel compositions varied from 1 to 86 ppm of the active substance (Ag) and were consistent with other research findings. The fungicidal effect was sufficiently  (3-30 times) lower for gel compositions based on ionic silver in comparison with colloidal forms; whereas bactericidal properties for both agents were similar.